Prevalence of Malnutrition Among Under-Five Children in Lumbini Province, Nepal: Evidence from Community-Based Screening Program - Narayan Prasad Chaudhary; Swastika Poudel; Sandesh Paudel; Kumar Thapa; Roshan Lal Chaudhary; Asha Chaudhary; Radha Darlami; Man Bahadur Oli (Nepal Journal of Public Health, 2026)
Background: Malnutrition affects physical and cognitive growth and increases the risk of morbidity and mortality. This study assessed the prevalence of malnutrition among children under five years of age in Lumbini Province. Methods: This retrospective cross-sectional study analyzed secondary data collected in a screening program from March to July 2025. Nutritional indicators were measured by using WHO classification. The association between predictor variables was assessed by multivariate logistic regression using SPSS v. 25 software and odds ratio with 95% confidence interval. Results: Among 78,652 screened children under five years of age, 48% had at least one form of malnutrition, including stunting (40%), underweight (22%), wasting (7.5%), and overweight (4.6%). Muslim (AOR=2.36; 95% CI: 2.16-2.57) and Madhesi (AOR=2.17; 95% CI: 1.99-2.36) ethnicity, rural residence (AOR=1.05; 95% CI:1.01-1.09), mountainous (AOR=1.82; 95% CI:1.68-1.98) and hill (AOR=1.44; 95% CI:1.38-1.50) zones showed higher odds of stunting, while female sex was protective. Similarly, higher odds of wasting were observed in Muslim (AOR=1.30; 95% CI: 1.15-1.48), Madhesi (AOR=1.28; 95% CI: 1.13-1.45), Janjati (AOR=1.28; 95% CI: 1.19-1.38) and Dalit (AOR=1.18; 95% CI: 1.01-1.29) whereas female sex and hills/mountain zones were protective. Likewise, the higher odd of being overweight was reported in Muslims (AOR=2.25; 95% CI: 1.85-2.72), hill (AOR=2.62; 95% CI:2.36-2.92) and mountainous (AOR=2.13; 95% CI: 1.72-2.63) zones but age below 24 months and rural residence were protective. Conclusion: This study demonstrated a high burden of chronic undernutrition together with the presence of overweight among children under five years of age, indicating a double burden of malnutrition in Lumbini Province. Targeted nutrition interventions focusing on disadvantaged ethnic groups, rural communities, and food insecurity are needed.